G131 Identifying Neglect or Emotional Abuse in school aged children: A Systematic Review. (7th April 2014) - Williams, B; Naughton, A; Mann, M; Tempest, V; Kemp, A; Maguire, S
Abstract : Aim: Neglect is the most common form of maltreatment amongst school aged children which may impact on all aspects of their lives. This systematic review aims to define educational, emotional or behavioural features in children aged 5–13 years experiencing neglect or emotional abuse. Methods: Using 180 key words and phrases we searched 18 databases, six websites (1946–2012), and supplemented by hand searching journals and references. Of 5025 abstracts, 111 articles were reviewed by two independent reviewers (from a panel of paediatricians, teachers, educational and child psychologists, psychiatrists, and social workers), using standardised critical appraisal. Included: age 5 to 13 completed years, neglect or emotional abuse confirmed by explicit criteria. Excluded: outcome, management or mixed maltreatment categories. Results: Of 34 high quality comparative articles included, the study designs were: 19 case control, 12 longitudinal cohort, and 3 cross sectional. Educational features (9 articles) Neglected children had significantly lower IQ (3 of 4 articles), demonstrated less ability to carry out complex attention tasks requiring auditory attention, response set and visual-motor integration, but were better at problem solving, abstraction and planning than controls. Conflicting results emerged regarding numeracy, literacy and grade repetitions (2 articles). Emotional features (17 articles) In comparison to controls, Neglected children had lower self esteem (3 articles), higher perception of others being in control of their lives (1 article), more depressive symptoms and suicidal ideation (5 articles); Children who were neglected and emotionally abused showed lower understanding, recognition and regulation of emotions (5 articles). Behavioural features (14 articles) Neglected children exhibited anxious ambivalent attachment style (2 articles), more behavioural difficulties (3 articles), were more withdrawn (4 articles) than controls. Children who were neglected and emotionally abused displayed ADHD features (3 of 5 articles). There were 6 articles addressing social competence and peer interaction giving conflicting results. Disabled boys were more likely to experience emotional abuse or neglect (1 article) than controls. Conclusion: School aged children referred for evaluation of educational difficulties or behavioural problems, merit exploration of neglect or emotional abuse as an aetiology. Questioning children directly about self esteem, depression or their emotions may help reveal the neglect they are experiencing.